Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1902/jop.2015.150361
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Gingival Adhesion Molecules in Periodontitis: Theoretical In Silico, Comparative In Vivo, and Explanatory In Vitro Models

Abstract: Gene expression of gingival adhesion molecules in periodontitis is regulated by leukocyte transmigration, whereas the neutrophilic antimicrobial peptide HNP-1 is noted as a putative regulator of epithelial adhesion molecules. These observations contribute to the key mechanisms by which future biomarkers might be developed for periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Moreover, the proliferation and differentiation of keratinocytes to form multilayers and the synthesis of keratins have been found to be dependent on cell number density (Ryle et al 1989). By combining this information, our group recently demonstrated that gingival keratinocytes can survive, form monolayers, and produce adhesion proteins at least for 24 h when they are cultured at high densities on semi-permeable nitrocellulose membranes at a floating position on a semi-solid growth medium (Gürsoy et al 2016). In the present study, we hypothesized that keratinocyte stratification can be accelerated by culturing them at high cell densities at an air-liquid-solid interface, omitting the submerged growing and air lifting steps of common multilayer cell culture techniques.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, the proliferation and differentiation of keratinocytes to form multilayers and the synthesis of keratins have been found to be dependent on cell number density (Ryle et al 1989). By combining this information, our group recently demonstrated that gingival keratinocytes can survive, form monolayers, and produce adhesion proteins at least for 24 h when they are cultured at high densities on semi-permeable nitrocellulose membranes at a floating position on a semi-solid growth medium (Gürsoy et al 2016). In the present study, we hypothesized that keratinocyte stratification can be accelerated by culturing them at high cell densities at an air-liquid-solid interface, omitting the submerged growing and air lifting steps of common multilayer cell culture techniques.…”
Section: Introductionmentioning
confidence: 93%
“…The more processes are integrated in the form of subnetworks in the interactome, the more accurate will our in silico model be to reflect the molecular pathogenesis of periodontal inflammation. An alternative possibility is, however, that other markers could also act as central members over the threshold upon the integration of additional subnetworks in the model, representing deregulated biological processes in periodontitis (e.g., epithelial cell adhesion; Haapasalmi et al, 1995 ; Gürsoy et al, 2015 ). These newly developed subnetworks might also be considered in the future as part of a systems biology approach utilized in different fields of medicine such as cancer, neurodegenerative, and psychiatric diseases (Rosado et al, 2011 ; Santana-Codina et al, 2013 ; ElRakaiby et al, 2014 ; Podder and Latha, 2014 ; Zeidán-Chuliá et al, 2014b ; Ebhardt et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“… 9 The network of adhesion molecules in protein–protein interactions in gingival epithelial cells provides a clear picture for understanding the regulation of TJ proteins in periodontitis. 10 …”
Section: Introductionmentioning
confidence: 99%